Major adverse cardiovascular events in patients after acute myocardial infarction treated invasively and different patterns of glucometabolic disturbances evaluated at mid-term follow-up - Francuz, Paweł; Podolecki, Tomasz; Kozieł, Monika; Kalarus, Zbigniew; Kowalczyk, Jacek (Journal of Medical Science, 2017)
Objective:  To assess the impact of glucometabolic status (GS) evaluated at hospital discharge and at mid-term follow-up visit (FU-visit) on major adverse cardiovascular events (MACE) in patients (pts) with acute myocardial infarction (AMI) treated invasively.Material and Methods: Study encompassed 368 AMI-pts treated invasively, in whom GS was assessed by 2-hour post load glycemia at hospital discharge and at FU-visit after 6 months. Patients were divided into two groups with respect to GS at hospital discharge: abnormal glucose tolerance (AGT, n=149), normal glucose tolerance (NGT, n=219). Each of those groups was divided into two subgroups with respect to GS at FU-visit: persistent AGT (pAGT, n=101), transient AGT (tAGT, n=48), newly detected AGT (newAGT, n=114), persistent NGT (pNGT, n=105). Median follow-up duration after FU-visit was 24.5 months.Results: There was a trend towards more subjects with MACE in AGT than NGT group (24.2% vs. 16%; p=0.051). More AGT-pts were hospitalized due to decompensated heart failure (6% vs. 0.5%; p=0.002). However, there were no significant differences in MACE between subjects with pAGT and tAGT, including heart failure hospitalizations. Among NGT-pts there were no significant differences in particular MACE between newAGT-pts and pNGT-pts.Conclusions: In AMI-pts treated invasively, who had abnormal glucose tolerance at hospital discharge, the improvement in glucometabolic status after 6 months was not related to lower risk of hospitalization due to decompensated heart failure.